2020
DOI: 10.1002/pd.5754
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal evaluation and postnatal outcomes of fetal ovarian cysts

Abstract: To evaluate the natural history and outcome of cases of fetal ovarian cyst under conservative prenatal treatment. A retrospective cohort study included patients diagnosed with fetal ovarian cysts was conducted between January 2008 to December 2016. Data including clinical data, sonographic feature and postnatal outcomes were obtained. One hundred and two cases were included for statistical analysis. The rate of spontaneous resolution was significantly higher among cases with simple than complex cysts (70/92 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 26 publications
1
21
0
1
Order By: Relevance
“…This cyst grows rapidly, and it fills the entire abdominal cavity after birth. Seven simple cysts in our study resolved prenatally or postnatally, just like previous studies reported 17 . Another 5 cases that were shown to be torsion postnatally were found to have a complex ultrasound appearance in the antenatal period.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This cyst grows rapidly, and it fills the entire abdominal cavity after birth. Seven simple cysts in our study resolved prenatally or postnatally, just like previous studies reported 17 . Another 5 cases that were shown to be torsion postnatally were found to have a complex ultrasound appearance in the antenatal period.…”
Section: Discussionsupporting
confidence: 83%
“…Seven simple cysts in our study resolved prenatally or postnatally, just like previous studies reported. 17 Another 5 cases that were shown to be torsion postnatally were found to have a complex ultrasound appearance in the antenatal period. This stresses the importance of prenatal and postnatal ultrasound scans to monitor changes in ovarian cysts.…”
Section: Reproductive Systemmentioning
confidence: 99%
“…In addition, cysts were divided into simple and complex cysts according to their US characteristics. 3 Anechoic, unilocular, smooth, and thin-walled cysts were defined as simple cysts. Multiloculated, thick-walled cysts containing echogenic or solid components and septa were defined as complex cysts (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…However, theca lutein and corpus luteum cysts may rarely develop. 3 Although the risk factors are not well known, fetal ovarian cysts are more common in pregnancies that are complicated by diabetes mellitus, preeclampsia and Rh isoimmunization. 4 Fetal ovarian cysts are generally diagnosed in the third trimester.…”
Section: Introductionmentioning
confidence: 99%
“…Los quistes ováricos son la tercera causa más importante de masas intraabdominales después de los sistemas renal y gastrointestinales, podrían confundirse con quistes genitourinarios, quistes gastrointestinales y linfangiomas (1) (2) (3). La prevalencia de quistes ováricos en recién nacidos es de 1 en 1000 nacidos vivos (4). La incidencia real no está determinada, pero puede observarse en 30 -70 % de fetos, mediante la ecografía prenatal de rutina.…”
Section: Introductionunclassified